AIDS-related deaths of children in Larkana district: Act now or regret later. - Nitik Sharma; Arsalan Hyder; Sikander Ali (Journal of the Pakistan Medical Association, 2021)
The district Larkana has faced multiple outbreaks in the past decade. AIDS-related deaths of children in the Larkana district since the 2019 outbreak of HIV has increased with the potential to rise even more in the future. This article discusses the stigma associated with HIV in rural areas of Sindh Province and emphasizes ways to promptly deal with these situation. Continuous...